Battling the plantation mentality : Memphis and the Black freedom struggle - Green, Laurie B. (Laurie Beth) (John Hope Franklin series in African American history and culture., 2007)
African American freedom is often defined by emancipation and civil rights legislation, but it did not arrive with the stroke of a pen or the rap of a gavel. This book argues that no single event makes this plainer than the 1968 Memphis sanitation workers' strike, which culminated in the assassination of Martin Luther King Jr. It demonstrates that the civil rights movement was battling an ongoing 'plantation mentality' based on race, gender, and power, which permeated southern culture long before - and even after - the groundbreaking legislation of the mid-1960s.